A opressão da criança em Graciliano Ramos e Charles Dickens - Santos, Elizabete Maria Alvares dos (2017)
The main aspect of this work is to elaborate a comparative study between Charles Dickens and Graciliano Ramos, initially chosen, respectively, for their works: Oliver Twist and Infância. Our comparative work presents some of the common aspects and distances between these authors and their works. On the course of our work, we present the profile of each novelist and their socio-historical scenarios, from their distinct formations to realities represented by the Western Literature of the 19th and 20th centuries, respectively. Initially, our main aim is on the child exploitation and the violence inflicted on them. However, due to societies so infinitely different, the concepts and representations of "child" and childhood are very different from each other. Throughout our work, we have taken care to separate the memorial, the historiographical, the autobiographical, especially regarding to the aesthetics of their literary works, the reason for our study. “Remembrance”, in the concepts of Jeanne Marie Ganegbin, gives theoretical support to our study, as well as the ones from Eliane Zagury which support the relation of autobiography as an expression bias of the memory reports. At the end of our research, we will be presenting the similarities between both authors, since they have lived, sometime in their lifetime, the narrative of violence in their works.